Birinci dünya savaşında Atatürk’ ün Güney Doğudaki faaliyetleri - Apak, Bekir (My University, 1998)
unknown
Keywords: Atatürk, Gazi Mustafa Kemal, Türkiye Cum. Bşk., 1, 1881-1938; Atatürk, Mustafa Kemal, President of the Republic of Turkey 1, 1881-1938